Phliantidae - Coleman, Charles Oliver (Zootaxa, 2009)
Pereionotus thomsoni Stebbing is redescribed based on new material from the Great Barrier Reef. This phliantid amphipod has a depressed body. It can be recognized by mid-dorsal hump-like carinae and the typical shape of the basis of pereopod 7 which is constricted posterodistally.